Effects of dentin surface preparations on bonding of self-etching adhesives under simulated pulpal pressure - Chantima Siriporananon; Pisol Senawongse; Vanthana Sattabanasuk; Natchalee Srimaneekarn; Hidehiko Sano; Pipop Saikaew (Restorative Dentistry & Endodontics)
ObjectivesThis study evaluated the effects of different smear layer preparations on the dentin permeability and microtensile bond strength (µTBS) of 2 self-etching adhesives (Clearfil SE Bond [CSE] and Clearfil Tri-S Bond Universal [CTS]) under dynamic pulpal pressure.Materials and MethodsHuman third molars were cut into crown segments. The dentin surfaces were prepared using 4 armamentaria: 600-grit SiC paper, coarse diamond burs, superfine diamond burs, and carbide burs. The pulp chamber of each crown segment was connected to a dynamic intra-pulpal pressure simulation apparatus, and the permeability test was done under a pressure of 15 cmH2O. The relative permeability (%P) was evaluated on the smear layer-covered and bonded dentin surfaces. The teeth were bonded to either of the adhesives under pulpal pressure simulation, and cut into sticks after 24 hours water storage for the µTBS test. The resin-dentin interface and nanoleakage observations were performed using a scanning electron microscope. Statistical comparisons were done using analysis of variance and post hoc tests.ResultsOnly the method of surface preparation had a significant effect on permeability (p < 0.05). The smear layers created by the carbide and superfine diamond burs yielded the lowest permeability. CSE demonstrated a higher µTBS, with these values in the superfine diamond and carbide bur groups being the highest. Microscopic evaluation of the resin-dentin interface revealed nanoleakage in the coarse diamond bur and SiC paper groups for both adhesives.ConclusionsSuperfine diamond and carbide burs can be recommended for dentin preparation with the use of 2-step CSE.